Predictors of Relapse after Discontinuing Systemic Treatment in Childhood Autoimmune Chronic Uveitis. - Simonini, Gabriele; Bracaglia, Claudia; Cattalini, Marco; Taddio, Andrea; Brambilla, Alice; de Libero, Cinzia; Pires Marafon, Denise; Caputo, Roberto; Cimaz, Rolando (J Rheumatol, 2017)
OBJECTIVE: To identify clinical predictors of relapse in childhood autoimmune chronic uveitis after stopping systemic treatment. METHODS: A retrospective, multicenter, cohort study. RESULTS: Ninety-four children in remission, receiving no treatments and with at least a 6-month followup, were enrolled. A higher probability of maintaining remission after discontinuing treatment was shown in idiopathic compared with juvenile idiopathic arthritis uveitis (Mantel-Cox chi-square = 23.21) if inactivity had been obtained within 6 months from starting systemic treatment (Mantel-Cox chi-square = 24.17) and by antitumor necrosis factor-α treatment (Mantel-Cox chi-square = 6.43). CONCLUSION: Type of disease, time, and type of systemic therapy to achieve inactivity predict different duration of uveitis remission after treatment withdrawal.
Keywords: Adolescent; Antirheumatic Agents; Autoimmune Diseases; Child; Child, Preschool; Female; Humans; Male; Predictive Value of Tests; Recurrence; Retrospective Studies; Treatment Outcome; Uveitis; Withholding Treatment

Chronic nonbacterial osteomyelitis may be associated with renal disease and bisphosphonates are a good option for the majority of patients. - Pastore, Serena; Ferrara, Giovanna; Monasta, Lorenzo; Meini, Antonella; Cattalini, Marco; Martino, Silvana; Alessio, Maria; La Torre, Francesco; Teruzzi, Barbara; Gerloni, Valeria; Breda, Luciana; Taddio, Andrea; et al. (Acta Paediatr, 2016)
AIM: The aim of this Italian study was to describe the clinical features, treatment options and outcomes of a cohort of patients with chronic nonbacterial osteomyelitis (CNO). METHODS: This was a retrospective cohort study. Laboratory data, diagnostic imaging, histological features and clinical course are reported. RESULTS: We enrolled 47 patients diagnosed with CNO. Bone pain was the leading symptom, and multifocal disease was present in 87% of the patients. The majority of the bone lesions were located in the appendicular skeleton (58%). Extraosseous manifestations were present in 34% of the patients, and renal involvement was detected in four patients. Inflammatory indices were increased in 80%, and bone x-rays were negative in 15% of the patients. Nonsteroidal anti-inflammatory drugs (NSAIDs) were the first therapy for all patients, achieving clinical remission in 27%. A good response to NSAIDs was significantly associated with a better prognosis. Bisphosphonates were used in 26 patients, with remission in 73%. Only six patients (13%), all with spine involvement, developed sequelae. CONCLUSION: We found a possible association between CNO and renal disease. Bisphosphonates were more likely to lead to clinical remission when NSAIDs and corticosteroids had failed. Vertebral localisation was the only risk factor for potential sequelae.

Recent advances in the use of Anti-TNFα therapy for the treatment of juvenile idiopathic arthritis. - Taddio, Andrea; Cattalini, Marco; Simonini, Gabriele; Cimaz, Rolando (Expert Rev Clin Immunol, 2016)
Juvenile Idiopathic Arthritis (JIA) encompasses a group of diseases of unknown etiology having in common arthritis in at least 1 joint that persists for 6 weeks and begins before 16 years of age, with other conditions excluded. With a prevalence of 1 per 1,000 children in the USA, JIA is the most common pediatric rheumatic illness and a major cause of acquired childhood disability. During the last 20 years, the advent of host immune response modifiers known as biologic agents, in particular the anti-TNFα agents (etanercept, infliximab, adalimumab), which directly inhibit the action of pro-inflammatory mediators, has revolutionized the treatment and the expected outcome of JIA. This article highlights treatment indications of anti-TNFα drugs and their more frequent side effects in JIA patients.

Follow-up and quality of life of patients with cryopyrin-associated periodic syndromes treated with Anakinra. - Lepore, Loredana; Paloni, Giulia; Caorsi, Roberta; Alessio, Maria; Rigante, Donato; Ruperto, Nicola; Cattalini, Marco; Tommasini, Alberto; Zulian, Francesco; Ventura, Alessando; Martini, Alberto; Gattorno, Marco (J Pediatr, 2010)
OBJECTIVE: To evaluate the quality of life and long-term follow-up of patients enrolled in the Italian registry of cryopyrin-associated periodic syndromes (CAPS). STUDY DESIGN: Since 2004, 20 patients with CAPS were enrolled in a common registry from different Italian Centers of Pediatric Rheumatology; 14 patients were treated with Anakinra in an open fashion. Both treated and untreated patients were routinely followed according to standard of care. The Child Health Questionnaire (CHQ-PF 50) was used to assess the health-related quality of life. RESULTS: The mean duration of follow-up was 37.5 months. In all treated patients, a complete and persistent control of the inflammatory manifestations was observed with no further progression of the disease. At enrollment in the registry, patients showed a poorer health-related quality of life than healthy children in both physical and the psychosocial summary scores. Treatment was associated with a dramatic and sustained amelioration of a variety of measures of poor quality of life, particularly in those concerning the global health perception, bodily pain-discomfort, and other physical domains. CONCLUSIONS: Long-term IL-1 blockade produces a significant and persistent improvement in the clinical manifestations associated with the disease and on the overall quality of life.
Keywords: Adolescent; Adult; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Follow-Up Studies; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-1; Male; Phenotype; Quality of Health Care; Quality of Life; Questionnaires; Syndrome; Treatment Outcome